C. T Scan Findings in Mild Traumatic Head Injury in Adults - Alamgir Khan; Sultan Jalal-ud-din Faisal (Journal of Rawalpindi Medical College, 2018)
Background: To determine the frequency of CT scan findings in patients having mild traumatic head injury (THI). Methods: In this cross sectional study all cases with mild traumatic injury to head were included . All the included patients were assessed by taking detailed history, especially about mode of injury and clinical examination including assessment of consciousness with Glasgow coma scale. CT scan of brain was done of all patients in order to detect any injury like Acute subdural hematoma, skull fractures, subgaleal hematoma, brain swelling, sub arachnoid hemorrhage, brain contusions and extradural hematoma. Results:- A total of 396 cases were studied, their average age was 26.93±7.07 years. CT scan findings in mild TBI are; brain swelling (3.28%), skull fracture (6.31%), subgaleal hematoma (13.13%), subarachnoid hemorrhage (13.38%), brain contusion (14.9%), acute subdural hematoma. No significant difference was found in CT scan findings according to age groups, gender and duration of injury. Conclusion: Commonest finding of CT in present study is subdural hematoma followed by extradural hematoma